Integrating Telemedicine into Family Medicine Practice: Impact on Access and Continuity of Primary Care - Gricelda Emperatriz Valencia Olalla; Pedro Renato Flores Brito; Lucy Maria Padilla Torres; Angel Mamani-Ruelas (International Journal of Medical Toxicology and Legal Medicine, 2024)
Telemedicine has become a crucial tool to improve access to health care and ensure continuity in primary care, especially in family medicine. This study explores the impact of integrating telemedicine into family medicine practice and discusses how it influences patient access and continuity of care. Through a mixed approach to data analysis, the benefits and challenges perceived by patients and healthcare professionals over the past five years are examined. The results show that telemedicine has improved accessibility, especially in rural areas, and has facilitated continuity of care, although barriers related to infrastructure and training are identified. These findings suggest the need for supportive policies and ongoing education to optimize the use of telemedicine in family medicine.